Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/phar.1799
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hospital Readmission in Patients Receiving Outpatient Parenteral Antimicrobial Therapy

Abstract: Readmissions while patients received OPAT were common. Therefore, proactive interventions including primary care physician assignment to facilitate follow-up and communication should be implemented to decrease the risk of readmission, particularly in the identified high-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 13 publications
2
44
1
Order By: Relevance
“…Twenty‐six studies published between 1997 and 2016 analysed the safety and effectiveness of OPAT services. This included 3 prospective studies without comparison group and 23 retrospective studies without comparison group . Nine studies were performed in Europe, eight in the USA, two in Australia, two in New Zealand, two in Singapore, one in Canada, one in Saudi Arabia and one in Israel .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty‐six studies published between 1997 and 2016 analysed the safety and effectiveness of OPAT services. This included 3 prospective studies without comparison group and 23 retrospective studies without comparison group . Nine studies were performed in Europe, eight in the USA, two in Australia, two in New Zealand, two in Singapore, one in Canada, one in Saudi Arabia and one in Israel .…”
Section: Resultsmentioning
confidence: 99%
“…In the study performed by Steinmetz et al, only 30% of the total patients’ data files were reviewed for complications (21%). Similarly, Means et al considered only 144 cases out of 216 when reporting cure rate (70%). Rehm and Longworth evaluated only 52.8% of the total patients treated in the period for outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study of 230 patients receiving OPAT via a PICC, the overall 60-day HCU incidence rate was 27%, in the range found in previous OPAT studies [6, 7, 12, 13]. Yan et al recently conducted a single-center retrospective cohort study of 104 patients discharged on OPAT and reported an all-cause 60-day HCU rate of 43%, 26% of whom were readmitted to the hospital [6].…”
Section: Discussionmentioning
confidence: 72%
“…Many patients are discharged on OPAT for the treatment of osteomyelitis and endocarditis, and since the recommended treatment for these diagnoses may be greater than four weeks, it is important to evaluate beyond 30 days. Means et al performed a retrospective cohort study and found that 20% of OPAT patients experienced a hospital readmission, although this study did not specify the duration of follow-up [7]. In our study, both inpatient hospital readmissions and ED visits were included in the endpoint as both indicate an exacerbation in a patient’s health status and may represent a failure of OPAT as a step-down approach.…”
Section: Discussionmentioning
confidence: 97%